Inteferensi Bahasa Indonesia terhadap Bahasa Inggris yang Digunakan oleh Para Staff Hotel dan Restoran di Daerah Pariwisata Candidasa - Anak Agung Gede Oka Geria; Dewa Gde Bawa (Unit Pelayanan Bahasa, Politeknik Pariwisata Bali, 2022)
Research on the interference of mother tongue to second language has attracted the interest of bilingual researchers. Most of their research is related to second language learning. However, language interference that occurs in hotel and restaurant workers is still an area that has not been studied much. Therefore, this study aims to identify the interference that occurs in the use of the English language of hotel and restaurant staff in the Candidasa tourist area, Bali. By using a qualitative approach, data collection was carried out on the conversations that occurred between hotel and restaurant staff and the tourists they served. The conversations were recorded and analyzed. The results of the study indicate that there is interference between the Indonesian language and the English used, namely word choice interference, phonological interference and grammatical interference.